2013 IEEE Workshop on Automatic Speech Recognition and Understanding 2013
DOI: 10.1109/asru.2013.6707749
|View full text |Cite
|
Sign up to set email alerts
|

Improvements to Deep Convolutional Neural Networks for LVCSR

Abstract: Deep Convolutional Neural Networks (CNNs) are more powerful than Deep Neural Networks (DNN), as they are able to better reduce spectral variation in the input signal. This has also been confirmed experimentally, with CNNs showing improvements in word error rate (WER) between 4-12% relative compared to DNNs across a variety of LVCSR tasks. In this paper, we describe different methods to further improve CNN performance. First, we conduct a deep analysis comparing limited weight sharing and full weight sharing wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
108
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(109 citation statements)
references
References 13 publications
0
108
0
1
Order By: Relevance
“…Several strategies exist for this, the classic one being maxpooling [7], but other, more sophisticated pooling formulas have also been proposed. For example, Abdel-Hamid et al investigated weighted softmax pooling [11], while Sainath et al studied p-norm pooling and stochastic pooling [12]. However, none of these proved significantly better than simple max-pooling.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
See 4 more Smart Citations
“…Several strategies exist for this, the classic one being maxpooling [7], but other, more sophisticated pooling formulas have also been proposed. For example, Abdel-Hamid et al investigated weighted softmax pooling [11], while Sainath et al studied p-norm pooling and stochastic pooling [12]. However, none of these proved significantly better than simple max-pooling.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…In the full weight sharing scheme (FWS), all neurons are applied across all spectral regions, so the neurons encounter a more elaborate learning task. However, Sainath et al argue that with a large enough number of hidden units, FWS can attain the same performance as LWS, while it is technically simpler and allows the stacking of convolutional layers [12]. In this study, we applied limited weight sharing, which is shown in Fig.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
See 3 more Smart Citations